Peer-Based Intervention in Improving Social Interaction of Autistic Children - Afifah, Aisyah Nisaul; Palem, Angela Elsani Dian; Bagis, Inayah Nisrin Salim; Mufadhilah, Nadia Diana Ummi; Novianti, Ranti (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2024)
This study is a literature review of peer-based interventions in improving social interaction in children with Autism Spectrum Disorder (ASD). Using a literature review approach, we searched for relevant literature to identify the effect of peer-based interventions in overcoming difficulties in children with Autism Spectrum Disorder (ASD) in their social interactions. The literature search was conducted through credible search engines such as Google Scholar, PubMed, and others. The search includes keywords such as "autism spectrum disorder" "peer mediated intervention" "social skill" "interaction skill" and other variations with a period of 2019-2023. The results of this study indicate that peer-based interventions can improve social engagement in children with ASD. Factors such as similar interests, support and positive feedback from peer coaches, and adult monitoring play a role in the success of the intervention. Although there is variation between studies, these findings provide a strong basis for understanding the important role of interest-based interventions in supporting the development of social interactions in children with ASD. Practical implications include the need for individualized approaches and integration of interest-based interventions into special education programs. This study also identifies knowledge gaps and recommends future research directions to continue to enrich our understanding of effective intervention strategies to improve social interaction skills in children with Autism Spectrum Disorder (ASD).